2008
DOI: 10.1016/j.tsf.2007.10.082
|View full text |Cite
|
Sign up to set email alerts
|

Carrier transport in polycrystalline ITO and ZnO:Al II: The influence of grain barriers and boundaries

Abstract: Seebeck coefficient measurements as a function of the carrier concentration give hints to different transport mechanisms in ITO and ZnO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
120
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(130 citation statements)
references
References 39 publications
8
120
0
2
Order By: Relevance
“…The contribution of the grain boundaries to electron scattering is believed to be entirely screened out by the contribution of the bulk of the crystallites. 4 The aforementioned is supported by Ellmer and Mientus, 5 Minami et al, 6 Steinhauser et al, 7 and Ruske et al 8 Minami et al 6 have concluded that grain boundary scattering is mainly dominant in AZO films with carrier concentrations in the range 10 19 -10 20 cm À3 while the ionized impurity scattering is dominant in layers with carrier concentrations in the range 10 20 -10 21 cm À3 . Steinhauser et al 7 concluded that the grain boundaries do not limit the conductivity for carrier concentrations exceeding 1 Â 10 20 cm À3 based on the comparison between Hall mobility and optical mobility for boron-doped ZnO.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The contribution of the grain boundaries to electron scattering is believed to be entirely screened out by the contribution of the bulk of the crystallites. 4 The aforementioned is supported by Ellmer and Mientus, 5 Minami et al, 6 Steinhauser et al, 7 and Ruske et al 8 Minami et al 6 have concluded that grain boundary scattering is mainly dominant in AZO films with carrier concentrations in the range 10 19 -10 20 cm À3 while the ionized impurity scattering is dominant in layers with carrier concentrations in the range 10 20 -10 21 cm À3 . Steinhauser et al 7 concluded that the grain boundaries do not limit the conductivity for carrier concentrations exceeding 1 Â 10 20 cm À3 based on the comparison between Hall mobility and optical mobility for boron-doped ZnO.…”
Section: Introductionmentioning
confidence: 83%
“…That developed by Tarng 19 based on the assumption of Schottky thermionic emission and then followed by Bruneaux et al 4 for degenerate materials is l g ¼ BT expðÀU a =k B TÞ; (5) or ln(l g =T) $ ÀT À1 . Note that B is a constant related to the grain size and electron concentration and U a is the activation energy given by U b À (E F À E C ).…”
Section: Grain Boundary Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…6.г, 7 -1 Ом•см відповідно при рості тиску в камері осадження з 0,1 Па до 0,3 Па. Оскільки високолеговані прозорі провідні матеріали поводять себе як метали, в яких концентрація носіїв не залежить від температури, а енергія легуючих домішок дорівнює нулю, то процеси розсіювання в останніх стають такими як і в металевих плівках [38]. Тож на питомий опір плівок ZnO:Al впливає поверхневе розсіювання, розсіювання на домішках і дефектах, та розсіювання на границях зерен [39].…”
Section: рис 5залежність зсуву бурштейна-моссаunclassified
“…Тож на питомий опір плівок ZnO:Al впливає поверхневе розсіювання, розсіювання на домішках і дефектах, та розсіювання на границях зерен [39]. Загалом варто відмітити, що, як правило, дуже важко розділи вплив поверхневого розсіювання та розсіювання на границях зерен в тонких полікристалічних плівках [38]. В нашому випадку, коли структурна досконалість плівок ZnO:Al зі зменшенням тиску кисню в камері осадження покращується: збільшується розмір зерен, що відповідає зменшенню питомого опору (збільшенню провідності) за рахунок зниження розсіювання на границях зерен (більші зерна -менше границь зерен), правомірно стверджувати, що при тисках кисню на рівні 0,03 -0,1 Па визначальним впливом на значення питомого опору плівок ZnO:Al однакової товщини є розсіювання на границях зерен.…”
Section: рис 5залежність зсуву бурштейна-моссаunclassified